Histórias de vida na periferia : juventudes e seus entrecruzamentos - Bardi, Giovanna (Universidade Federal de São Carlos, 2013)
The drug issue today has been represented by an alarming debate characterized by the disqualification of many people who use those substances. The discussion, commonly, is focused on problematizations around a poor youth, on which there is an imbued approach by lack, by criminalization or by the concentration of attention on fighting products, losing sight of the sociocultural details of their uses. From a perspective contrary to the simplistic association between poor youngsters and drug use, it was aimed to know the life histories of young residents of a medium-sized city in the interior of Sao Paulo, Sao Carlos (SP), who use illicit drugs and consider that they need assistance in this using, seeking to identify their personal and social networks, formal and informal, that this population has accessed for assistance regarding such use, or even networks that are imposed into their lives. As a methodological resource, it was performed a monitoring of two young participants from previous activities of projects connected to the University coming from teaching, research and extension nature, resuming previously established contacts and following them up for a period of one year through an ethnographic analysis of field data, achieved through the immersion in their daily lives and the writing of field diaries to reflect on that reality. We also sought to access the agents cited by youngsters as present on their networks, to conduct semi-structured interviews with them. At last categories of analysis to be discussed were raised, according to the theoretical and methodological assumptions of Social Occupational Therapy, Sociology and Anthropology. The results showed the importance of these networks in the aid facing difficult situations due to the use of drugs, especially those from informal nature. We emphasize the aid granted to the people belonging to religious temples however this was not found to be related to attachment to divinities, a fact that puts in check speeches about the "salvation" of drug users by faith. Networks of formal stamp showed "just" in the modalities of admission via therapeutic community and containment through a regional police station. Thus recognizing that the study of networks can point out to potential ways of approach to the drug phenomenon, we hope to contribute with assumptions for the formulation of more consistent with reality public policies, which can effectively act as social supports in the life of those youngsters.
Keywords: Terapia ocupacional; Drogas e juventude; Redes sociais; Terapia ocupacional social; Juventude; História de vida; Youth; Histories of Life; Drugs; Social Occupational Therapy; Social Networks; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL